2017
DOI: 10.1177/1359104517713240
|View full text |Cite
|
Sign up to set email alerts
|

Associations between family and clinician ratings of child mental health: A study of UK CAMHS assessments and outcomes

Abstract: Background: The rated severity of child mental health problems depends on who is doing the rating, whether child, carer or clinician. It is important to know how these ratings relate to each other. Aims:To investigate to what extent clinicians' views are associated with carers' and young people's views in routine care in the United Kingdom. Method: Ratings of clinician and parent/child viewpoints from a large Child and Adolescent Mental Health Services (CAMHS) sample (ns 1773-47,299), as measured by the Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, it should be noted that, as shown also recently (Terrelonge & Fugard, 2017), for more effective screening, it is appropriate to associate the collection of data from other sources ("multi-informant assessment"), such as teachers and minors themselves, through self-administered tools, especially if they are adolescents…”
Section: Screening On Large Populationsmentioning
confidence: 99%
“…On the other hand, it should be noted that, as shown also recently (Terrelonge & Fugard, 2017), for more effective screening, it is appropriate to associate the collection of data from other sources ("multi-informant assessment"), such as teachers and minors themselves, through self-administered tools, especially if they are adolescents…”
Section: Screening On Large Populationsmentioning
confidence: 99%
“…86 Terrelong and Fugard (2017) demonstrated the importance of multi-informant data gathering and integrating multiple clinician perspectives when monitoring outcomes. 151 Welsh et al (2011) identified a need for further training for CAMHS clinicians in relation to the psychosis risk syndrome. 208 One study assessed symptoms and tracked progress 197 using the HoNOSCA to assess global functioning.…”
Section: Impact On Mental Health Assessment Processes and Outcomesmentioning
confidence: 99%
“…health crisis tools for general population of children/adolescents Child Anxiety Life Interference Scale, Children's Revised Impact of Events Scale and Children's Global Assessment230 Predictors of change in global psychiatric functioning at an inpatient adolescent psychiatric unit229 Compares clinician rating on CGAS and family ratings on SDQ151 …”
mentioning
confidence: 99%
“…Furthermore, the current service evaluation did not include clinician assessed outcomes, parent/guardian assessed outcomes, or teacher ratings. Outcomes were therefore based solely on the children and young peoples' self-reported change, and consequently lacked multiinformant data and the combination of multiple perspectives recommended when monitoring outcomes (Terrelonge and Fugard, 2017). Goal-based outcomes were, however, collaboratively rated during therapeutic sessions.…”
Section: Limitationsmentioning
confidence: 99%